SARS knowledge portal / Maizatul Akmar Ismail and Nor Edzan Che Nasir - Ismail, Maizatul Akmar; Che Nasir, Nor Edzan (2004)
Severe Acute Respiratory syndrome or SARS for short is a respiratory illness that brings about atypical pneumonia in infected patients. A knowledge portal for SARS will be developed in order to disseminate information and act as an interactive web site that offers a broad array of resources and services to the public, especially to Malaysian. The inspiration of developing the portal is due to arising problem regarding method of distributing information about SARS and lack of public awareness towards the jeopardy of the disease. Rich Internet Application (RIA) technology will be integrated together with the porta] which will enables all information and services offerd being displayed in a single screen layout. Rich Internet Applications offer the benefits of distributed, server-based Internet applications with the rich interface and interaction capabilities of desktop applications. The key difference between a typical Flash site and an RIA is that RlAs possess the functionality to interact with and manipulate data, rather than simply visualize or present it.